2009
DOI: 10.1248/bpb.32.2057
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inhibiting the Proteasomal Degradation of Estrogen Receptor .ALPHA. on Estrogen Receptor .ALPHA. Activation under Hypoxic Conditions

Abstract: Estrogen receptor (ER) a is a member of the nuclear receptor superfamily. Upon binding to 17b-estradiol (E2), ERa undergoes conformational changes and modulates the transcription of target genes.1) The magnitude of this estrogen-induced response depends on the initial concentration of ERa 2) and is modulated by numerous regulatory proteins.3) Furthermore, the differential regulation of coactivator activity modulates ER signal transduction pathways via direct or indirect interactions.4) Despite considerable pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Several published studies have shown that ERα can undergo proteosome-mediated degradation (Levi-Montalcini et al, 1996,Petrel and Brueggemeier, 2003). Therefore, we examined the effect of the widely used ubiquitin-proteosome inhibitor, MG-132, on ERα protein levels (Park et al, 2009,Kretzer et al, 2010). Given that E2 did not have a major effect on ERα protein levels, for these studies, we cultured Pyk2-KO and WT OBs without E2, for 4 days and then added 20 μM MG-132 for the final 3 hours of culture.…”
Section: Resultsmentioning
confidence: 99%
“…Several published studies have shown that ERα can undergo proteosome-mediated degradation (Levi-Montalcini et al, 1996,Petrel and Brueggemeier, 2003). Therefore, we examined the effect of the widely used ubiquitin-proteosome inhibitor, MG-132, on ERα protein levels (Park et al, 2009,Kretzer et al, 2010). Given that E2 did not have a major effect on ERα protein levels, for these studies, we cultured Pyk2-KO and WT OBs without E2, for 4 days and then added 20 μM MG-132 for the final 3 hours of culture.…”
Section: Resultsmentioning
confidence: 99%